Methods of Trace Mineral Supplementation - Matthew J. Hersom; Todd A. Thrift (EDIS)
Trace minerals supplementation is an integral component of the total diet for beef cattle. Trace minerals from the diet function in many of the metabolic processes associated with animal growth, health, and reproduction. It is essential that cattle have access to trace minerals in their diet. However, the forage cattle consume as the bulk of their diet is often deficient in trace mineral concentrations. Therefore, cattle need to be supplemented with trace minerals on a regular basis. Cattle producers can choose from a number of different methods to supplement trace minerals to cattle. Each method has characteristic advantages and disadvantages. The value of the characteristics should be evaluated against management activities of each cattle producer to determine the optimal trace mineral delivery strategy.